La educación como herramienta de combate. De Sócrates a Paulo Freire - Polo Blanco, Jorge (2018)
“Education as a Tool for Combat. From Socrates to Paulo Freire”. In this paper, without seeking to be exhaustive, we intend to take a journey which will enable us to see what a concept of education closely linked to the independence of the “voice of reason” has meant in different historical contexts; we understand this independence, very broadly speaking, as a critical capacity which enables us as human beings to be sufficiently free and, if necessary (as it almost always is), to be able to construct autonomously our own judgments in the face of the inertial weight of tradition and the force of the social consensuses which structure the common sense of our time. We can trace this “enlightened tension” through the history of Western thought from Plato to Condorcet, from Kant to Paulo Freire. In this sense, and to conclude, it will be appropriate to assess what role the educational process is taking on in the contemporary era, where the intensive processes of commodification have also come to permeate all aspects of knowledge.